Antibacterial activity of the novel peptide Pac-525 with the RGD motif against intracellular Escherichia coli - Coufalova, Martina; Rodrigo, Miguel A M; Michalkova, Hana; Milosavljevic, Vedran; Hrazdilova, Kristýna; Zurek, Ludek; Cihalova, Kristyna (Scientific reports, 2025)
Infections caused by invasive intracellular bacteria pose major therapeutic challenges due to pathogen survival and growth inside of host cells as well as the low intracellular accessibility for conventional antibiotics. The limited ability of most antibiotics to enter intracellular compartments underscores the urgent need for innovative antimicrobial agents capable of overcoming these barriers. In this study, the antibacterial peptide Pac525 was synthesized with the RGD domain to facilitate efficient penetration into eukaryotic cells. The efficacy and safety of RGD-Pac525 was evaluated in intracellular infection models, using the macrophage cell line RAW 264.7, chicken intestinal organoids, and chicken embryo tissues via the chorioallantoic membrane (CAM). Our findings from cell line experiments demonstrate that the RGD-Pac525 peptide retained the antimicrobial properties of the original peptide without compromising its efficacy. While RGD-Pac525 reduced the intracellular adherent-invasive pathogen Escherichia coli KV203 by 50% in RAW 264.7 macrophage cells, it did not adversely affect the macrophage viability. Additionally, RGD-Pac525 effectively reduced the intracellular bacterial burden in organoids, without compromising their structural integrity. In ovo bioassays, a substantial reduction in the bacterial load was observed in liver and intestinal tissues, indicating the peptide ability to achieve systemic distribution and to overcome tissue barriers. RGD-Pac525 was effective in infection models by suppressing bacterial growth. Preliminary observations suggest it may also affect host responses, indicating a potential for combined antimicrobial and therapeutic effects that warrant further studies. This study provides a compelling proof of concept for utilizing RGD-modified antimicrobial peptides for treatment of intracellular bacterial infections.
Keywords: Microbial Sensitivity Tests; infekce vyvolané Escherichia coli; Escherichia coli Infections; Organoid; Intracellular infections; CAM assay; Oligopeptides; Antibacterial peptide; makrofágy; mikrobiální testy citlivosti; Antimicrobial Peptides; antimikrobiální peptidy; Escherichia coli; antibakteriální látky; zvířata; myši; oligopeptidy; kuřecí embryo; Mice; Chick Embryo; RAW 264.7 buňky; Anti-Bacterial Agents; Organoids; organoidy; RGD-Pac525; Animals; Macrophages; RAW 264.7 Cells